Organizational Climate Assessment of Trust, Knowledge, Learning, and Motivation of Agile Teams - A Case Study - Dutra, Eliezer; Cerdeiral, Cristina; Lima, Patrícia; Diirr, Bruna; Santos, Gleison (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Organizational climate management is challenging for organizations developing Management Information Systems (MIS). Turnover, legacy code maintenance, delivery of fixed deadlines, lack of domain knowledge influences team trust, learning, and member motivation. Organizational climate surveys can provide concrete evidence of how the process, project activities, people, and culture work in practice. Problem: Not assessing specific human factors that contribute to the formation of agile teams’ climate inhibits the capacity for an assertive diagnosis, entailing difficulties for the analysis of possible causes of problems and the execution of corrective actions within climate management. Solution: We present the preliminary evaluation of TACT, an instrument to assess the organizational climate of agile teams, considering the Trust, Knowledge, Learning, and Motivation. IS Theory: Agile Software Development Methods (ASDM) and their effects. Method: TACT was developed using Design Science Research. We executed a case study in a Brazilian and a Canadian organization. We evaluated TACT using quantitative and qualitative methods. Summary of Results: TACT captured that the product owner's lack of knowledge and experience probably influenced the adverse climate in team trust and that unrealistic deadlines may have generated a lack of team motivation due to an absence of autonomy to plan the iteration. The team leaders reported intention of future use. Contributions and Impact in the IS area: TACT dimensions presented high levels of reliability and can be used to better identify issues and improve actions aligned with the agile values, principles, and practices while developing Information Systems.